A retrospective review of an epidural blood patch database: the incidence of epidural blood patch associated with obstetric neuraxial anesthetic techniques and the effect of blood volume on efficacy. (February 2017) - Booth, J.L.; Pan, P.H.; Thomas, J.A.; Harris, L.C.; D'Angelo, R.
Highlights: The effectiveness of epidural blood patch over 15 years was reviewed retrospectively. This represents the largest number of procedures from a single institution in the literature. It was hypothesized that increasing blood volume would increase effectiveness of an epidural blood patch. Increasing blood volume up to 30 mL did not reduce the need for repeat epidural blood patch. Abstract: Background: The optimal volume of blood required to treat post-dural puncture headache remains in question. In our institution a target volume of 30 mL is used for an epidural blood patch unless the patient experiences pain during injection. Methods: The institutional database was retrospectively reviewed for epidural blood patch and delivery statistics over a 15-year period to determine if the volume of blood administered during the procedure directly correlated with the number of epidural blood patches administered. The primary endpoint was defined as the need for a repeat epidural blood patch. Results: There were 466 epidural blood patches performed on 394 patients, associated with 84 804 obstetric neuraxial procedures. Thirty-two percent (95% CI 28.3 to 34.9%) of patients who had an inadvertent dural puncture with an epidural needle received an epidural blood patch versus 0.19% (0.16% to 0.22%) of patients who received neuraxial anesthesia with no documented dural puncture with an epidural needle. All patients experienced relief of post-dural puncture headache, although 17% required two and 1.5% required three epidural blood patches. The mean ± SD volume of blood administered was 20.5 ± 5.4 mL and only 35 patients (8.9%) received 30 mL. Conclusion: Increasing blood volumes up to 30 mL did not reduce the need for repeat epidural blood patch. Although the optimal volume of blood to administer during epidural blood patch placement remains unknown, our institution will continue to administer up to 30 mL or until the patient experiences pain during epidural injection.